The Bobbsey Twins at Snow Lodge - Hope, Laura Lee (Salt Lake City, UT : Project Gutenberg, 2004)
"The Bobbsey Twins at Snow Lodge" by Laura Lee Hope is a children's novel written during the early 20th century. This tale is part of a beloved series that follows the adventures of the Bobbsey twins as they navigate various settings and escapades. The story unfolds with the younger twins, Flossie and Freddie, engaging in wintertime fun with their pet dog Snap, as the family anticipates a vacation at a place called Snow Lodge. At the start of the book, the Bobbsey twins express excitement and innocence as they prepare for a sled ride with Snap, highlighting their adventurous spirit. The opening chapter introduces a playful scene where they endeavor to harness Snap for sledding and ultimately face a humorous mishap when they tumble into a snowbank. Following this, the presence of their older siblings, Bert and Nan, is established, revealing a close-knit family dynamic. As the narrative progresses, the children encounter a frantic situation involving runaway horses and the mysterious character of Mr. Carford, who carries a past tied to the family's history. This opening sets the stage for further adventures and connections to Snow Lodge, fostering curiosity and anticipation as the story unfolds. (This is an automatically generated summary.)
Release date is 2004-07-01
Produced by Juliet Sutherland, Charles Franks and the Online Distributed Proofreading Team
Keywords: Twins -- Juvenile fiction; Bobbsey Twins (Fictitious characters) -- Juvenile fiction; Siblings -- Juvenile fiction